Effect of Educational Intervention on Perceived Susceptibility Self-Efficacy and DMFT of Pregnant Women - Shahnazi, Hossein (Iran Red Crescent Med J, 2016)
BACKGROUND: The World Health Organization identifies oral health as a necessity for public health through the entirety of life. This issue has been considerably addressed due to susceptibility to tooth decay during pregnancy and maternal and fetal health. OBJECTIVES: Investigate the effect of educational intervention on perceived susceptibility, self-efficacy, and DMFT of pregnant women. PATIENTS AND METHODS: A quasi-experimental survey (pretest, posttest, and control group) was implemented in 88 primiparous women in the first trimester of pregnancy who attended private clinics in Delfan city, Iran. It was conducted using random sampling and then assigned to intervention and control groups. Data were collected using a questionnaire that included demographic characteristics, a DMFT checklist, and some health belief model (HBM) constructs. After collecting baseline information, an educational intervention consisting of 4 training sessions for the intervention group was scheduled. In the sessions, lecture, focus-group discussion, video, and role-playing were used as the main educational strategies. Four months after the intervention, a post-test questionnaire and DMFT checklist were conducted. Data were analyzed using SPSS (ver20) software and Chi-square, independent t-test, and repeated measure ANOVA at the significant level of α < 0.05. RESULTS: According to the independent t-test, the mean score of knowledge, perceived susceptibility, self-efficacy, and DMFT was not different between the two groups before the education (P > 0.05), during the intervention, or after intervention. Repeated measure ANOVA explained that the aforementioned score was different in the three cases (pretest, 2 months after intervention, and 4 months after intervention) after intervention (P < 0.05). Paired t-test also showed that the DMFT mean increased 4 months after intervention in the control group (P < 0.001). It was not, however, augmented in the intervention group (P = 0.92). CONCLUSIONS: Results showed that education on some of the HBM constructs resulted in increased knowledge of oral health, perceived susceptibility, and self-efficacy of pregnant women. It is also possible to prevent increased DMFT during pregnancy.